Reducing Metabolic Syndrome Risk Using a Personalized Wellness Program. Issue 12 (December 2015) - Steinberg, Gregory; Scott, Adam; Honcz, Joseph; Spettell, Claire; Pradhan, Susil
Abstract : Objective: The aim of this study was to determine the impact of a targeted, personalized wellness program on reducing employees' future risk of metabolic syndrome. Methods: Aetna piloted a year-long program that included a limited genetic profile, a traditional psychosocial assessment, and high-intensity coaching in a randomized controlled study of Aetna employees with an increased risk for metabolic syndrome. Results: Sustained employee engagement of 50% over the course of 1 year; 76% of participating employees lost an average of 10 pounds (4.5 kg) ( P  < 0.001 vs baseline weight), and there were trends in improved clinical outcomes relative to three of five metabolic factors. Average health care costs were reduced by $122 per participant per month, resulting in a positive return on investment in the program's first year. Conclusions: At scale, such programs would be expected to lead to significant downstream reduction in major clinical events and costs.